2021
DOI: 10.1073/pnas.2020990118
|View full text |Cite
|
Sign up to set email alerts
|

Plant virus evolution under strong drought conditions results in a transition from parasitism to mutualism

Abstract: Environmental conditions are an important factor driving pathogens’ evolution. Here, we explore the effects of drought stress in plant virus evolution. We evolved turnip mosaic potyvirus in well-watered and drought conditions in Arabidopsis thaliana accessions that differ in their response to virus infection. Virus adaptation occurred in all accessions independently of watering status. Drought-evolved viruses conferred a significantly higher drought tolerance to infected plants. By contrast, nonsignificant inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 57 publications
2
63
0
2
Order By: Relevance
“…Some viruses are clearly beneficial to their infected host, protecting them from heat and/or water scarcity [ 1 , 30 , 31 , 32 ]. Increasing amounts of studies demonstrated the way viruses manage to increase the plant’s response to environmental stresses (reviewed in [ 33 ]). For example, four different RNA viruses, brome mosaic virus (BMV), cucumber mosaic virus (CMV), tobacco mosaic virus (TMV), and tobacco rattle virus (TRV), were shown to improve the infected plant’s tolerance to drought [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses are clearly beneficial to their infected host, protecting them from heat and/or water scarcity [ 1 , 30 , 31 , 32 ]. Increasing amounts of studies demonstrated the way viruses manage to increase the plant’s response to environmental stresses (reviewed in [ 33 ]). For example, four different RNA viruses, brome mosaic virus (BMV), cucumber mosaic virus (CMV), tobacco mosaic virus (TMV), and tobacco rattle virus (TRV), were shown to improve the infected plant’s tolerance to drought [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several mosquito viruses can be transmitted vertically, although whether they are fixed in populations or stable on evolutionary timescales is not well investigated. Like other endosymbionts, the interactions between mosquito viruses and their hosts can be diverse, and the outcomes of these interactions may be context-dependent, as shown for a plant virus that confers drought tolerance to its hosts when evolved in drought conditions ( González et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant viruses adapt to compatible hosts and vectors under specific climates [16,19,33]. On the one hand, climate change and global trade can facilitate the appearance of outbreaks of new viruses in crops and regions where they were not previously present.…”
Section: Discussionmentioning
confidence: 99%